2004
DOI: 10.1097/01.pdm.0000133154.73846.66
|View full text |Cite
|
Sign up to set email alerts
|

PolyA PCR Amplification of cDNA from RNA Extracted from Formalin-Fixed Paraffin-Embedded Tissue

Abstract: RNA extraction still relies almost exclusively on the use of fresh or frozen tissue, limiting the number of samples that can be analyzed, and there is a growing need for means of global mRNA analysis of archived formalin-fixed paraffin-embedded tissue (FFPET). Previous reports of RNA extraction and amplification from FFPET are limited and do not enable global cDNA amplification. This study used polyA PCR to generate globally amplified cDNA from RNA extracted from formalin-fixed paraffin-embedded samples. RNA w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 12 publications
0
13
0
1
Order By: Relevance
“…However, most tumor samples are stored in paraffin blocks and the RNA in these tissues is strongly degraded (39), which may lead to a loss of detectable mRNA because RNA breaks can occur in between the location of the primers used. To set up a system which works with RNA from paraffin-embedded tissue it is necessary to either choose primer couples generating very small amplicons so that at least some of the extracted RNA can be amplified (40,41), or use newly developed protocols for fixation that prevent strong degradation (42).…”
Section: Discussionmentioning
confidence: 99%
“…However, most tumor samples are stored in paraffin blocks and the RNA in these tissues is strongly degraded (39), which may lead to a loss of detectable mRNA because RNA breaks can occur in between the location of the primers used. To set up a system which works with RNA from paraffin-embedded tissue it is necessary to either choose primer couples generating very small amplicons so that at least some of the extracted RNA can be amplified (40,41), or use newly developed protocols for fixation that prevent strong degradation (42).…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was then extracted an RNeasy mini kit (Qiagen), as recommended by the manufacturer; DNase was used to remove the contaminating genomic DNA, and polyA RT-PCR was carried out as previously described. 13,[19][20][21] Global amplification of cDNA corresponding to all expressed genes (polyA PCR) was carried out as previously reported. [19][20][21] …”
Section: Extraction Of Rna and Global Amplification Of Polyadenylatedmentioning
confidence: 99%
“…12 The polyA cDNA pool generated is also indefinitely renewable and as such represents a "molecular block." [11][12][13] The polyA cDNA can be then be assayed for the expression of particular genes, either by hybridization with cDNA microarrays 14 or by real-time PCR. Real-time PCR measurement, however, enables more precise quantitation of the expression levels of specific Indicator genes.…”
Section: Introductionmentioning
confidence: 99%
“…In the early 1990s, several groups reported that DNA and RNA remained well preserved in FFPE and could be extracted for PCR amplification, although the mRNA size would be substantially reduced. [9][10][11][12] Only recently have researchers succeeded in developing protein extraction methods for FFPE tissues. 6,[13][14][15] However, these processes are destructive and require several hours, substantial amounts of tissues, and high salt concentrations in order to achieve satisfactory protein yields for SDS-PAGE analysis.…”
mentioning
confidence: 99%